Electrochemically modified carbon fiber brush composite silver oxygen reduction electrode and preparation method thereof
The electrochemically modified carbon fiber brush composite silver oxygen reduction electrode addresses the limitations of seawater batteries by enhancing electrocatalytic activity and anti-fouling, resulting in improved oxygen reduction performance and specific power density.
Patent Information
- Application Number
- CN202411183478.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
Existing seawater batteries face challenges with low dissolved oxygen concentration, poor cathode material activity, low working current density, and large cathode area requirements, leading to low specific power density and large battery volume.
An electrochemically modified carbon fiber brush composite silver oxygen reduction electrode is prepared by weaving polyacrylonitrile-based carbon fiber tow and titanium wire, followed by electrochemical treatment with aniline to introduce nitrogen-containing active functional groups and depositing silver, enhancing electrocatalytic activity and anti-fouling properties.
The modified electrode exhibits high electrocatalytic activity, anti-fouling performance, good conductivity, and low material cost, with improved oxygen reduction performance and increased specific power density, suitable for seawater batteries and other applications.
Smart Images

Figure CN119194485A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical ocean energy for in-situ electricity generation using seawater, and in particular to an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode and a preparation method thereof. Background Art
[0002] Seawater dissolved oxygen battery is referred to as seawater battery (SWB), in which seawater is used as electrolyte and dissolved oxygen in seawater is used as cathode reaction active substance, oxygen reduction reaction (ORR) occurs on positive carbon fiber brush electrode, magnesium anode dissolution reaction occurs with high-activity magnesium alloy as negative electrode, and continuous supply of oxygen and elimination of byproducts on electrode surface (cathode product-calcium carbonate and anode product-magnesium hydroxide) are achieved under the action of ocean current, thus forming a primary battery. Since dissolved oxygen in seawater is inexhaustible and the large amount of magnesium ions contained in it can be refined and regenerated, it can be considered as an environmentally friendly and renewable chemical ocean energy.
[0003] Seawater batteries have significant features (no need to carry electrolytes, energy density up to 700Wh Kg -1 , open structure, high safety) have shown great advantages in the marine field. However, the existing seawater batteries also have prominent disadvantages: low dissolved oxygen concentration in seawater, poor activity of cathode materials; low working current density of the battery, poor specific power density; large cathode area required for high power output, resulting in a large battery volume. Therefore, the core issue of developing advanced seawater batteries is how to significantly increase the specific power density.
[0004] In order to overcome this limitation, the selection of positive electrode materials is particularly important. After the carbon fiber is made into a brush-shaped electrode, it can not only reflect the material's own high strength, corrosion resistance, large specific surface area and excellent chemical stability, but also has a compact structure, soft stretching in seawater, low resistance to ocean currents and anti-scouring. However, commercialized polyacrylonitrile-based carbon fiber (PANCF) is inert and has weak catalytic activity for ORR, resulting in large electrode polarization and low battery output voltage, which limits the increase in output power. Chinese invention patent CN104838051B provides a solution for oxygen- and nitrogen-co-doped polyacrylonitrile-based carbon fiber and its preparation method, which uses electrochemical modification to oxidize the inherent pyridine nitrogen on the surface of the carbon fiber to a pyridine azone structure, thereby having electrocatalytic properties for ORR. However, the electrocatalytic ability of the above solution for ORR still needs to be further improved, and the problem of anti-biological fouling of the positive electrode material also needs to be solved when used in nearshore and shallow seas.
[0005] In summary, the development of a seawater dissolved oxygen battery cathode with both high catalytic activity and anti-fouling performance is still a key issue that needs to be urgently solved in the field of chemical ocean energy that utilizes seawater to generate electricity in situ. Summary of the invention
[0006] In order to make up for the deficiencies of the prior art, the present invention provides an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode and a preparation method thereof.
[0007] The present invention is achieved through the following technical scheme: a method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode, which specifically comprises the following steps: a carbon fiber brush electrode is made by weaving raw materials of polyacrylonitrile-based carbon fiber tow and titanium wire; the carbon fiber brush electrode is placed in an electrolyte solution containing aniline, and after cyclic treatment between electrochemical oxidation and electrochemical reduction, an electrochemically modified carbon fiber brush electrode with nitrogen-containing active functional groups on the surface is prepared; the electrochemically modified carbon fiber brush electrode is placed in a silver nitrate solution, and silver is deposited through electrochemical reduction to obtain an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode.
[0008] As a preferred embodiment, the electrolyte solution containing aniline is one or a combination of aqueous solutions of sulfuric acid, sodium sulfate, potassium sulfate, ammonium sulfate, ammonium bicarbonate, sodium nitrate and potassium nitrate with an aniline concentration of 0.1-10 mM.
[0009] As a preferred embodiment, the cyclic treatment steps of electrochemical oxidation and electrochemical reduction in an electrolyte solution containing aniline are as follows: placing a carbon fiber brush electrode in an electrolyte solution containing aniline, an oxygen evolution reaction accompanied by water electrolysis occurs on the electrode surface during the electrochemical oxidation treatment; a hydrogen evolution reaction accompanied by water electrolysis occurs on the electrode surface during the electrochemical reduction treatment; and cyclic treatment is performed between the above-mentioned electrochemical oxidation and electrochemical reduction to obtain the electrochemically modified carbon fiber brush electrode.
[0010] As a preferred embodiment, the nitrogen-containing active functional group is one or a combination of pyridinic nitrogen, 2-hydroxypyridinic nitrogen and graphitic nitrogen at the edge of the carbon-based surface of the polyacrylonitrile-based carbon fiber; one or more of the nitrogen-containing active functional groups have a synergistic electrocatalytic effect on the oxygen cathode reduction reaction after being compounded with metallic silver.
[0011] As a preferred solution, based on the mass of the raw material polyacrylonitrile-based carbon fiber tow, the total electrochemical oxidation charge is 1000-10000 C / g, and the total electrochemical reduction charge is 1000-10000 C / g.
[0012] As a preferred embodiment, the total electrochemical oxidation quantity in the cyclic treatment process between electrochemical oxidation and electrochemical reduction is greater than or equal to the total electrochemical reduction quantity.
[0013] As a preferred embodiment, silver is electrochemically reduced and deposited in a silver nitrate solution, and the electrochemical reduction deposition charge is 50-500 C / g based on the mass of the raw material polyacrylonitrile-based carbon fiber tow, thereby obtaining the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode.
[0014] An electrochemically modified carbon fiber brush composite silver oxygen reduction electrode prepared by the preparation method of the present invention is made of raw material polyacrylonitrile-based carbon fiber tow and titanium wire through weaving into a brush-shaped electrode (carbon fiber brush electrode), and then prepared by electrochemical modification, so that its surface has an active layer composed of nitrogen-containing active functional groups and composite metal silver, wherein the nitrogen-containing active functional groups are obtained by cyclic treatment of electrochemical oxidation and electrochemical reduction in an electrolyte solution containing aniline, which is inherent in the raw material polyacrylonitrile-based carbon fiber and the nitrogen from aniline in the solution; wherein the composite metal silver is obtained by further electrochemically reducing the silver ions in the silver nitrate solution and depositing them on the electrode. The nitrogen-containing active functional groups in the active layer cooperate with the metal silver to have high electrocatalytic activity for ORR, and the metal silver also has the ability to resist marine biofouling. On the premise that the reaction can proceed smoothly, the technicians in this field can select and regulate the concentration and dosage of the above-mentioned supporting electrolyte solution according to the specific situation.
[0015] Due to the adoption of the above technical scheme, the present invention has the following beneficial effects compared with the prior art: the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode provided by the present invention has the characteristics of high electrocatalytic activity, anti-fouling, good conductivity, low material cost, excellent stability and long service life. The preparation method of the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode provided by the present invention has the advantages of simple manufacturing, low production cost and suitability for industrial production.
[0016] The electrochemically modified carbon fiber brush composite silver oxygen reduction electrode provided by the present invention can be used to manufacture the positive electrode of a seawater dissolved oxygen battery, and can also be expanded to be applied to electrodes used in other types of seawater batteries, proton exchange membrane fuel cells, metal-air fuel cells, microbial fuel cells, energy storage flow batteries, electrochemical sewage treatment and electrochemical sensors, as well as various electrochemical engineering technology fields using the electrode material.
[0017] Additional aspects and advantages of the present invention will become apparent from the following description or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 Schematic diagram of the structure of the oxygen reduction electrode of electrochemically modified carbon fiber brush composite silver; Figure 2 This is a scanning electron microscope (SEM) image of an oxygen reduction electrode of electrochemically modified carbon fiber brushed with composite silver; Figure 3 This is the X-ray diffraction (XRD) pattern of electrochemically modified carbon fiber brush composite silver; Figure 4 Polarization curves of electrochemically modified carbon fiber brush electrode and electrochemically modified carbon fiber brush composite silver electrode in 3.5wt% NaCl solution (under 700 rpm magnetic stirring condition); Figure 5 The chronoamperometric curves of the electrochemically modified carbon fiber brush electrode and the electrochemically modified carbon fiber brush composite silver electrode in 3.5 wt% NaCl solution (under 700 rpm magnetic stirring) at -0.4 V in different solutions; Figure 6 Polarization curves of electrochemically modified carbon fiber brush composite silver electrodes with different silver loadings in 3.5 wt% NaCl solution (under 700 rpm magnetic stirring conditions); Figure 7 The chronoamperometric curves of the electrochemically modified carbon fiber brush composite silver electrode with different silver loadings in 3.5 wt% NaCl solution (under 700 rpm magnetic stirring conditions) at -0.4 V. DETAILED DESCRIPTION
[0019] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0021] A method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode specifically comprises the following steps: preparing a carbon fiber brush electrode (brush-shaped electrode) by weaving raw materials of polyacrylonitrile-based carbon fiber tow and titanium wire; placing the carbon fiber brush electrode in an electrolyte solution containing aniline, and preparing an electrochemically modified carbon fiber brush electrode having nitrogen-containing active functional groups on the surface after cyclic treatment between electrochemical oxidation and electrochemical reduction; placing the electrochemically modified carbon fiber brush electrode in a silver nitrate solution, and depositing silver through electrochemical reduction to obtain an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode.
[0022] Preferably, the electrolyte solution containing aniline is one or a combination of sulfuric acid, sodium sulfate, potassium sulfate, ammonium sulfate, ammonium bicarbonate, sodium nitrate and potassium nitrate aqueous solutions with an aniline concentration of 0.1-10 mM. The composite metallic silver is prepared by placing the electrochemically modified carbon fiber brush electrode in an aqueous silver nitrate solution, and through electrochemical reduction, metallic silver is deposited on the surface of the electrochemically modified carbon fiber brush to form a discontinuous silver layer composed of silver particles, and then an active layer composed of composite metallic silver containing nitrogen-containing active functional groups is formed, and finally an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode is obtained.
[0023] Preferably, the cyclic treatment step of electrochemical oxidation and electrochemical reduction in an electrolyte solution containing aniline: placing a carbon fiber brush electrode in an electrolyte solution containing aniline, during the electrochemical oxidation treatment, an oxygen evolution reaction of water electrolysis occurs on the electrode surface; during the electrochemical reduction treatment, a hydrogen evolution reaction of water electrolysis occurs on the electrode surface; and cyclic treatment is performed between the above electrochemical oxidation and electrochemical reduction to obtain the electrochemically modified carbon fiber brush electrode. The above electrochemical oxidation and electrochemical reduction in an electrolyte solution containing aniline are different from the traditional electrochemical synthesis of polyaniline, and the intensity of its electrochemical oxidation and electrochemical reduction is higher, reaching the degree of oxygen evolution reaction and hydrogen evolution reaction of water electrolysis, respectively, and polyaniline cannot stably exist on the electrode surface. That is, the purpose of the present invention is to use aniline as a nitrogen source, and in the above electrochemical oxidation and electrochemical reduction cyclic treatment process, an electrochemical reaction occurs between aniline and carbon fiber, so as to enrich the types and quantities of the above nitrogen-containing active functional groups on the electrode surface, thereby improving the electrocatalytic activity for ORR.
[0024] Preferably, the nitrogen-containing active functional group is one or a combination of pyridinic nitrogen, 2-hydroxypyridinic nitrogen and graphitic nitrogen at the edge of the carbon-based surface of the polyacrylonitrile-based carbon fiber; one or more of the nitrogen-containing active functional groups have a synergistic electrocatalytic effect on the oxygen cathode reduction reaction after being compounded with metallic silver.
[0025] Preferably, the mass of the raw material polyacrylonitrile-based carbon fiber tow is used as a reference, the total electrochemical oxidation charge is 1000-10000 C / g, and the total electrochemical reduction charge is 1000-10000 C / g. In the above-mentioned cyclic treatment process between electrochemical oxidation and electrochemical reduction, the electrochemical oxidation and electrochemical reduction processes should be carried out alternately, but there is no restriction on whether the electrochemical oxidation process or the electrochemical reduction process is carried out first and last. In addition, there is no restriction on the number of cycles between electrochemical oxidation and electrochemical reduction, until the total electrochemical oxidation charge and the total electrochemical reduction charge meet the above requirements, the reaction can be stopped, and the electrochemically modified carbon fiber brush electrode is prepared. If the total electrochemical oxidation charge and / or the total electrochemical reduction charge is less than 1000C / g, the number of active functional groups in the active layer is small and the activity is low; if it is greater than 10000C / g, the active layer will be peeled off and damaged, and even the substrate structure will be damaged and lose activity.
[0026] Preferably, the total electrochemical oxidation amount in the cyclic treatment process between electrochemical oxidation and electrochemical reduction is greater than or equal to the total electrochemical reduction amount. There is no limitation on the amount of each electrochemical oxidation treatment and the amount of each electrochemical reduction treatment, and the amount of each electrochemical oxidation treatment may be greater than, equal to, or less than the amount of each electrochemical reduction treatment. Moreover, the amount of each electrochemical oxidation treatment may be the same or different, and the amount of each electrochemical reduction treatment may also be the same or different.
[0027] Preferably, silver is electrochemically reduced and deposited in a silver nitrate solution, and the electrochemical reduction deposition amount is 50-500 C / g based on the mass of the raw material polyacrylonitrile-based carbon fiber tow, to obtain the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode. If the electrochemical reduction deposition amount is less than 50C / g, the amount of composite silver in the active layer is small and the activity is low; if it is greater than 500C / g, a continuous silver layer composed of silver particles is formed, resulting in the weakening or even disappearance of the synergistic electrocatalytic effect of nitrogen-containing active functional groups and silver on ORR in the active layer, and the structure of the silver layer is prone to peeling and damage. In addition, on the premise that the reaction can proceed smoothly, the concentration of the silver nitrate solution can be selected and regulated by those skilled in the art according to the specific circumstances.
[0028] The schematic diagram of the oxygen reduction electrode structure of the electrochemically modified carbon fiber brush composite silver provided by the present invention is as follows Figure 1As shown, a brush-shaped electrode (carbon fiber brush electrode) is made by weaving titanium wire 1 and polyacrylonitrile-based carbon fiber bundle 2; the carbon fiber brush electrode is placed in an electrolyte solution containing aniline, and after a cyclic treatment between electrochemical oxidation and electrochemical reduction, an electrochemically modified carbon fiber brush electrode having nitrogen-containing active functional groups 3 on the surface of the polyacrylonitrile-based carbon fiber bundle 2 is obtained, wherein the nitrogen-containing active functional groups are obtained by cyclic treatment of electrochemical oxidation and electrochemical reduction of the nitrogen inherent in the raw material polyacrylonitrile-based carbon fiber and the nitrogen from aniline in the solution in the electrolyte solution containing aniline; the electrochemically modified carbon fiber brush electrode is placed in a silver nitrate solution, and silver 4 is deposited on the surface of the nitrogen-containing active functional group 3 through electrochemical reduction to obtain the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode. Among them, the nitrogen-containing active functional groups are one or a combination of pyridinic nitrogen, 2-hydroxypyridinic nitrogen and graphitic nitrogen at the edge of the carbon-based surface of the polyacrylonitrile-based carbon fiber; the active layer composed of nitrogen-containing active functional groups and deposited silver has a synergistic electrocatalytic effect on ORR; and the deposited silver also has the ability to resist marine biological fouling.
[0029] Combine the following Figures 2 to 7 The electrochemically modified carbon fiber brush composite silver oxygen reduction electrode and the preparation method thereof according to the embodiment of the present invention are specifically described.
[0030] Example 1 Firstly, 6g of T700SC 12K PAN-based carbon fiber tow and 2g of 1mm diameter titanium wire were woven into a carbon fiber brush electrode; then the carbon fiber brush electrode was placed in a 0.5 M sulfuric acid aqueous solution with an aniline concentration of 0.5 mM, and electrochemically anodic oxidation was performed for 5 minutes at a constant current density of ±2 A / g, and electrochemical cathode reduction was performed for 5 minutes, and then the above process was repeated 5 times to prepare an electrochemically modified carbon fiber brush electrode with nitrogen-containing active functional groups on the surface. During this period, the total oxidation charge passed was 3600 C / g (the total charge of 6 electrochemical oxidation processes), and the total reduction charge was 3600 C / g (the total charge of 6 electrochemical reduction processes); finally, the above electrochemically modified carbon fiber brush electrode was placed in a 0.1M silver nitrate solution, and the constant current density was -50 mA / g. The electrochemical reduction deposition time was 1h and the deposition charge was 180 C / g, and finally an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode with nitrogen-containing active functional groups and discontinuous silver particles on the surface was obtained.
[0031] Figure 2 The scanning electron microscope (SEM) photograph of the oxygen reduction electrode of the electrochemically modified carbon fiber brush composite silver provided in this embodiment shows that the silver particles deposited on the surface of the carbon fiber are discontinuously distributed and the particle size is uniform, about 400 nm. Figure 3This is the X-ray diffraction (XRD) spectrum of electrochemically modified carbon fiber brush composite silver. The positions of XRD diffraction peaks are located at 2θ=38.2°, 44.8°, 64.4°, and 77.5°, which correspond one to one with the diffraction peaks of Ag (PDF#89-3722) in the standard spectrum, confirming the presence of Ag in the electrode. The 25.8° wide diffraction peak corresponds to the disordered carbon structure formed by the electrochemically modified carbon fiber.
[0032] Figure 4 Polarization curves of the electrochemically modified carbon fiber brush electrode and the electrochemically modified carbon fiber brush composite silver electrode provided in this embodiment in 3.5 wt% NaCl solution (under 700 rpm magnetic stirring conditions). As can be seen from the figure, the oxygen reduction starting potential of the electrochemically modified carbon fiber brush composite silver electrode is -0.13V, compared with -0.21 V of the electrochemically modified carbon fiber brush electrode, the oxygen reduction starting potential after composite silver is more positive, positively shifted by 80 mV, and the polarization current density of the electrochemically modified carbon fiber brush composite silver electrode is larger, and the oxygen reduction performance is significantly improved. The nitrogen-doped carbon material formed by the electrochemically modified carbon fiber brush generally undergoes oxygen reduction reaction through a two-electron and four-electron mixed pathway; the presence of silver catalyzes the further decomposition of hydrogen peroxide produced by the two-electron pathway, performs an indirect four-electron process, and improves the oxygen reduction activity. On the other hand, the introduction of silver, as a new oxygen reduction active site, will enhance the ability to adsorb oxygen atoms in ORR, thereby obtaining a more positive oxygen reduction starting potential.
[0033] Figure 5The chronoamperometric curves of the electrochemically modified carbon fiber brush electrode and the electrochemically modified carbon fiber brush composite silver electrode in 0.5 M sulfuric acid aqueous solution without and with aniline at a concentration of 0.5 mM in 3.5 wt% NaCl solution (under 700 rpm magnetic stirring) at -0.4 V are provided in this embodiment. The platform current region corresponds to the reduction reaction of dissolved oxygen. The larger the current density in the platform region, the higher the oxygen reduction activity. It can be seen from the figure that the electrochemically modified carbon fiber brush composite silver electrode has the best oxygen reduction activity, with a platform current density of 450 mA g-1. Compared with the electrochemically modified carbon fiber brush electrode in aniline sulfuric acid solution, the oxygen reduction current density is increased to 1.5 times; compared with the electrochemically modified carbon fiber brush electrode in aniline sulfuric acid solution, the oxygen reduction current is increased to 2.6 times, a difference of about 280 mA g-1. On the one hand, it shows that compared with the traditional electrochemical modification treatment without aniline, the electrochemical modification treatment containing aniline enriches the types and quantities of nitrogen-containing active functional groups on the electrode surface, thereby improving the electrocatalytic activity for ORR, because the nitrogen-containing active functional groups are converted from the inherent nitrogen in the raw material polyacrylonitrile-based carbon fiber and the nitrogen from aniline in the solution. On the other hand, it shows that the deposited silver and the nitrogen-containing active functional groups formed after the electrochemical modification treatment play a synergistic role. Silver becomes a new active site, realizes the rapid transfer of electrons, and jointly promotes the oxygen reduction reaction.
[0034] Example 2 Firstly, 6 g of T800SC 24K PAN-based carbon fiber tow and 2 g of 1.5 mm diameter titanium wire were woven into a carbon fiber brush electrode. Then, the carbon fiber brush electrode was placed in a 2 M sulfuric acid aqueous solution with an aniline concentration of 2 mM, and electrochemically anodic oxidation was performed for 5 minutes at a constant current density of ±3 A / g, followed by electrochemical cathode reduction for 5 minutes. The above process was then repeated 3 times to prepare an electrochemically modified carbon fiber brush electrode with nitrogen-containing active functional groups on the surface. During this period, the total oxidation charge was 3600 C / g (the total charge of 4 electrochemical oxidation processes), and the total reduction charge was 3600 C / g (the total charge of 4 electrochemical reduction processes). Finally, the above electrochemically modified carbon fiber brush electrode was placed in a 0.5 M silver nitrate solution, and by changing the current density and deposition time of the electrochemical reduction, electrochemically modified carbon fiber brush composite silver oxygen reduction electrodes with deposited silver charges of 80 C / g, 180 C / g, 280 C / g and 380 C / g were prepared, respectively.
[0035] Figure 6Polarization curves of electrochemically modified carbon fiber brush composite silver electrodes with different silver loadings provided in this embodiment in 3.5wt% NaCl solution (under 700 rpm magnetic stirring conditions). As can be seen from the figure, the oxygen reduction starting potential of the composite electrode with a silver deposition charge of 180C / g is -0.13 V, the oxygen reduction starting potential is the most positive, the polarization current density is the largest, and the oxygen reduction activity is the best; the oxygen reduction starting potential of the composite electrode with a silver deposition charge of 80C / g is -0.17 V, which is about 40mV different, and the oxygen reduction starting potentials of the composite electrodes with silver deposition charges of 280C / g and 380C / g are -0.149 V and -0.152V, respectively, which are not much different. In general, when the deposited silver charge increases from 80 C / g to 180 C / g, the oxygen reduction activity of the composite electrode increases with the increase of the deposited silver charge. As the deposited silver charge further increases to 280 C / g, the oxygen reduction starting potential of the electrode shifts negatively, the polarization current density decreases, and the oxygen reduction activity decreases. When the deposited silver charge is further increased to 380 C / g, its polarization curve basically coincides with that of the composite electrode with a deposited silver charge of 280 C / g, and the oxygen reduction activity of the composite electrode has not been significantly improved.
[0036] Figure 7 The electrochemically modified carbon fiber brush composite silver electrode with different silver loadings provided in this embodiment is provided in a 3.5wt% NaCl solution (under 700 rpm magnetic stirring conditions) at -0.4 V. The oxygen reduction current in the platform area of the composite electrode with a deposited silver charge of 180C / g is the largest, which is about 450mA g-1, and the oxygen reduction activity is the best. The oxygen reduction current in the platform area of the composite electrode with a deposited silver charge of 80C / g is the smallest, which is about 310 mA g-1. From the trend point of view, when the deposited silver charge increases from 80C / g to 180C / g, the electrode oxygen reduction performance increases with the increase of the deposited silver charge, but when the deposited silver charge continues to increase to 280C / g, the oxygen reduction performance of the electrode decreases instead, and the oxygen reduction current decreases to about 350 mA g-1. The deposited silver charge is further increased to 380C / g, and the oxygen reduction current of the electrode is still about 350 mA g-1. Figure 7 The performance of each electrode shown in the chronoamperometric curve is Figure 6 The performance of each electrode shown in the polarization curve is highly consistent. Silver has an effect on improving the oxygen reduction performance of the composite material, but the more silver content, the better. The increase in silver will affect the particle size, size uniformity and distribution of silver particles in the composite electrode, thereby affecting the relevant performance of the material. If the electrochemical reduction deposition charge is small, the amount of composite silver in the active layer is small and the activity is low; if the electrochemical reduction deposition charge is too large, the silver particles will agglomerate and even form a continuous silver layer composed of silver particles, resulting in the weakening or even disappearance of the synergistic electrocatalytic effect of nitrogen-containing active functional groups and silver on ORR in the active layer.
[0037] Example 3 Firstly, 10 g of T700SC 12K PAN-based carbon fiber tow and 3 g of 2 mm diameter titanium wire were woven into a carbon fiber brush electrode; then the carbon fiber brush electrode was placed in a 1 M sulfuric acid aqueous solution with an aniline concentration of 0.2 mM, and electrochemical anodic oxidation was performed for 10 minutes at a constant current density of ±1 A / g, followed by electrochemical cathode reduction for 5 minutes, and then the above process was repeated 8 times to prepare an electrochemically modified carbon fiber brush electrode with nitrogen-containing active functional groups on the surface. During this period, the total oxidation charge passed was 5400 C / g (the total charge of 9 electrochemical oxidation processes), and the total reduction charge was 2700 C / g (the total charge of 9 electrochemical reduction processes); finally, the above electrochemically modified carbon fiber brush electrode was placed in a 0.1 M silver nitrate solution, and the constant current density was -100 mA / g. The electrochemical reduction deposition time was 1 h and the deposition charge was 360 C / g, and finally an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode with nitrogen-containing active functional groups and discontinuous silver particles on the surface was obtained.
[0038] The oxygen reduction electrode of the electrochemically modified carbon fiber brush composite silver of this embodiment is used as the positive electrode to manufacture a seawater dissolved oxygen battery. The battery consists of a magnesium anode rod located in the center as the negative electrode and a total of 60 oxygen- and nitrogen-co-doped carbon fiber brush positive electrodes arranged in two layers around it. The positive electrode is welded and fixed on a full titanium metal frame, and the negative electrode is fixed to the center of the frame by bolts with insulating protective sleeves. The frame size is 500 mm×500 mm×500mm, and the initial spacing between the positive and negative electrodes is 120 mm. The actual sea discharge test data of the battery is analyzed and compared with the commercial seawater battery SWB1200. The results show that the average output power of the battery is 2W, and the volume power density is 15W / m3. Compared with the volume power density of SWB1200 of 2.7 W / m3, the battery performance is better. It can be seen that since the seawater dissolved oxygen battery uses the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode of this embodiment as the positive electrode of the battery, the seawater dissolved oxygen battery has a smaller volume and higher volume power density than the prior art.
[0039] In the description of the present invention, the term "plurality" refers to two or more than two. Unless otherwise clearly defined, the orientation or positional relationship indicated by the terms "upper" and "lower" is based on the orientation or positional relationship shown in the drawings. It is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation of the present invention; the terms "connection", "installation", "fixation", etc. should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0040] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0041] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode, characterized in that , specifically including the following steps: The carbon fiber brush electrode is made by weaving the raw materials of polyacrylonitrile-based carbon fiber tow and titanium wire; The carbon fiber brush electrode is placed in an electrolyte solution containing aniline, and after a cycle treatment between electrochemical oxidation and electrochemical reduction, an electrochemically modified carbon fiber brush electrode having nitrogen-containing active functional groups on the surface is prepared; The electrochemically modified carbon fiber brush electrode is placed in a silver nitrate solution, and silver is deposited through electrochemical reduction to obtain an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode.
2. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that The aniline-containing electrolyte solution is one or a combination of aqueous solutions of sulfuric acid, sodium sulfate, potassium sulfate, ammonium sulfate, ammonium bicarbonate, sodium nitrate and potassium nitrate with an aniline concentration of 0.1-10 mM.
3. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that The cyclic treatment steps of electrochemical oxidation and electrochemical reduction in the electrolyte solution containing aniline are as follows: placing the carbon fiber brush electrode in the electrolyte solution containing aniline, and during the electrochemical oxidation treatment, an oxygen evolution reaction accompanied by water electrolysis occurs on the electrode surface; during the electrochemical reduction treatment, a hydrogen evolution reaction accompanied by water electrolysis occurs on the electrode surface; and cyclic treatment is performed between the above-mentioned electrochemical oxidation and electrochemical reduction to obtain the electrochemically modified carbon fiber brush electrode.
4. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that The nitrogen-containing active functional group is one or a combination of pyridinic nitrogen, 2-hydroxypyridinic nitrogen and graphite nitrogen at the edge of the carbon-based surface of the polyacrylonitrile-based carbon fiber; one or more of the nitrogen-containing active functional groups have a synergistic electrocatalytic effect on the oxygen cathode reduction reaction after being combined with metallic silver.
5. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that , based on the mass of the raw material polyacrylonitrile-based carbon fiber tow, the total electrochemical oxidation charge is 1000-10000 C / g, and the total electrochemical reduction charge is 1000-10000 C / g.
6. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that , the total electrochemical oxidation quantity in the cyclic treatment process between the electrochemical oxidation and the electrochemical reduction is greater than or equal to the total electrochemical reduction quantity.
7. The method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode according to claim 1, characterized in that The electrochemical reduction deposition of silver in the silver nitrate solution is based on the mass of the raw material polyacrylonitrile-based carbon fiber tow, and the electrochemical reduction deposition charge is 50-500 C / g to obtain the electrochemically modified carbon fiber brush composite silver oxygen reduction electrode.
8. A method for preparing an electrochemically modified carbon fiber brush composite silver oxygen reduction electrode, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.